2007
DOI: 10.1097/01.ccm.0000281451.73202.f6
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor promotes physical wound repair and is anti-apoptotic in primary distal lung epithelial and A549 cells

Abstract: In addition to its known effects on endothelial cells, VEGF acts as a growth and anti-apoptotic factor on alveolar epithelial cells. VEGF treatment may have potential as a rescue therapy for diseases associated with alveolar epithelial damage such as acute respiratory distress syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 33 publications
4
50
0
Order By: Relevance
“…AT-2 cells were stimulated with hydrogen peroxide (H 2 O 2 , 0.5 mM, Xilong Chemical Factory, China). A dose of H 2 O 2 was chosen that was consistent with previous reports [28,29] and with our pilot study, in which we found that a lower dose (0.25 mM) of H 2 O 2 did not induce obvious AT-2 cells injury. At 0, 1, 2, 4, 8, 16, 24 h after treatment, cells were harvested and mRNA and protein was extracted to determine FoxA1 expression.…”
Section: Cell Culture and Induction Of Acute Cell Injurysupporting
confidence: 54%
“…AT-2 cells were stimulated with hydrogen peroxide (H 2 O 2 , 0.5 mM, Xilong Chemical Factory, China). A dose of H 2 O 2 was chosen that was consistent with previous reports [28,29] and with our pilot study, in which we found that a lower dose (0.25 mM) of H 2 O 2 did not induce obvious AT-2 cells injury. At 0, 1, 2, 4, 8, 16, 24 h after treatment, cells were harvested and mRNA and protein was extracted to determine FoxA1 expression.…”
Section: Cell Culture and Induction Of Acute Cell Injurysupporting
confidence: 54%
“…VEGF has autocrine effects on growth and proliferation of pulmonary epithelial cells in vitro and may protect against oxidant-induced apoptosis of cultured primary lung epithelial cells and epithelial-derived cell lines (38,60). Moreover, VEGF stimulates branching morphogenesis of renal tubular epithelium in culture (61).…”
Section: Discussionmentioning
confidence: 99%
“…Because VEGF, a Nrp1 ligand, promotes cell survival (38,59) and acts as a mitogen for both epithelial (60-62) and endothelial (63) cells, we measured the concentration of VEGF in both lung lavage and tissue lysates. As indicated in Figure 6 (top panel), levels of VEGF in lung lavage fluid did not differ significantly between conditionally Nrp1-deficient mice and littermates maintained in FA.…”
Section: Effects Of Cs Exposure and Pulmonary Epithelial Nrp1 Deletiomentioning
confidence: 99%
“…In the alveolar epithelium, VEGF was localized at the luminal surface of alveolar walls, mostly in alveolar epithelial type II cells (57). In vitro, A549 cells as well as primary rat alveolar epithelial cells express VEGF transcripts and their receptors Flk-1 and Flt-1 (6,38,45). The transcripts correspond to the three major VEGF isoforms previously described: VEGF 121 and VEGF 165 that are secreted in a soluble form and VEGF 189 that remains cell surface associated or is primarily deposited in the extracellular matrix (6).…”
Section: Na Transportersmentioning
confidence: 99%
“…Second, VEGF may exert autocrine or paracrine regulatory roles through the functional VEGF receptors present on alveolar epithelial cells (8). Thus, in lung explants, VEGF modulates epithelial cell proliferation and surfactant protein expression, and, in A549 cells, VEGF promotes wound repair and is antiapoptotic (45). Finally, because VEGF receptor-1 (Flt-1) has been reported to be present on monocytes/macrophages, the activation of which leads to monocyte activation and chemotaxis (11), it could be hypothesized that apical secretion of VEGF may play a role in the recruitment of immune cells in the alveolar space.…”
Section: Na Transportersmentioning
confidence: 99%